Strengthening primary health care in rural western India-team based approach - Roy, Kallol; Das, Neha; Roy, Swati A. (International Journal of Research in Medical Sciences, 2023)
Background: Non-communicable diseases (NCDs), such as cardiovascular diseases (CVDs), diabetes, have taken an epidemic form. With a huge population and existing sedentary lifestyle, in developing countries like India, there exists a struggle to deliver quality chronic care. A reorganization of systems in healthcare service delivery is crucial to improve primary healthcare. We have reported our model to address primary healthcare service delivery in rural settings. The SPARSH team-based care approach is designed with the objective of improving adherence to anti-hypertensive and anti-diabetic medications to improve blood pressure (BP) and blood sugar (BS) control among hypertension (HTN) and diabetes mellitus (DM) patients. Methods: This is a descriptive study describing a model and array on interventions delivered through a team-based care approach from 2016 till 2020 by Shree Krishna Hospital, Karamsad across three districts in Gujarat. Data was collected on case record forms and later was analysed using Microsoft excel. Results: From the financial year of 2016 till 2020 patients enrolled in SPARSH increased from 932 till 1920 for availing treatment and ongoing care. A total of 108 training sessions were conducted and facilitated by a senior member of SPARSH. Average monthly cost of treatment for hypertensive, diabetic and patients with both conditions was Rs. 38, 78 and 130 respectively. Conclusions: Our model described here can be tested for effectiveness through a rigorous community trial focusing on objective outcome measures such as BP control and glycemic control.